2015
DOI: 10.1063/1.4935418
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared electroluminescence from InAs type-I quantum wells grown on InAsP/InP metamorphic buffers

Abstract: We report room-temperature (RT) electroluminescence (EL) from InAs/InAs x P 1Àx quantum well (QW) light-emitting diodes (LEDs) over a wide wavelength range of 2.50-2.94 lm. We demonstrate the ability to accurately design strained InAs QW emission wavelengths while maintaining low threading dislocation density, coherent QW interfaces, and high EL intensity. Investigation of the optical properties of the LEDs grown on different InAs x P 1Àx metamorphic buffers showed higher EL intensity and lower thermal quenchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…37 Although grading GaAs x P 1-x buffers all the way to pure GaAs may increase the final TDD, yet, a combination of TCA and compositional step-grading scheme remains a promising approach to achieve a TDD of $1 Â 10 6 cm À2 . 45 In conclusion, we have presented the MBE growth of GaAs buffer layers on on-axis (001) GaP/Si substrates. ECCI measurements showed that the TDD in the optimized GaAs layer is 7.2 Â 10 6 cm À2 , which is a factor of $40 reduction compared with the unoptimized GaAs layer.…”
Section: Discussionmentioning
confidence: 93%
“…37 Although grading GaAs x P 1-x buffers all the way to pure GaAs may increase the final TDD, yet, a combination of TCA and compositional step-grading scheme remains a promising approach to achieve a TDD of $1 Â 10 6 cm À2 . 45 In conclusion, we have presented the MBE growth of GaAs buffer layers on on-axis (001) GaP/Si substrates. ECCI measurements showed that the TDD in the optimized GaAs layer is 7.2 Â 10 6 cm À2 , which is a factor of $40 reduction compared with the unoptimized GaAs layer.…”
Section: Discussionmentioning
confidence: 93%
“…Graded InAsP buffers grown by MBE have been studied as another platform for high-quality InAs type-I QWs by providing low threading dislocation densities of 2-4× 10 6 cm -2 and smooth surface morphology [103]. Furthermore, InAsP alloys on InP have a higher E g than InGaAs at the same lattice constant and thus offer more favorable carrier confinement in the QWs; Jung et al showed a barrier-emission-free EL peak from 2.5 μm to 3.0 μm at RT for InAs type-I QWs surrounded by InAs x P 1−x barriers with x=0.49-0.73 [108]. More recently, 2.75 μm RT lasing has been achieved in InAs/InAsP MQWs grown on InAs 0.5 P 0.5 multi-functional metamorphic buffers (MFMBs), as shown in figure 9 [107].…”
Section: Inp-based Type-i and Type-ii Emittersmentioning
confidence: 99%
“…In parallel, significant effort has been dedicated to extending the wavelength range accessible using InP-based devices [20]. This has involved the development of a variety of novel heterostructures, based on (i) type-II structures incorporating In x Ga 1−x (N)As/GaAs y Sb 1−y QWs (where pulsed-mode operation has been demonstrated out to 2.6 μm at 270 K) [21,22], or (ii) combining growth on Al x In 1−x As or InAs 1−x P x metamorphic buffer layers with highly-strained In x Ga 1−x As, InAs 1−x Sb x , GaSb 1−x Bi x or InAs 1−x Bi x type-I QWs (where pulsed-mode operation of a 2.9 μm device at 230 K has recently been demonstrated) [23][24][25][26][27][28][29]. Despite these ongoing innovations in heterostructure design and fabrication, pushing the emission wavelength of InP-based diode lasers beyond 3 μm remains a significant challenge.…”
Section: Introductionmentioning
confidence: 99%